A novel electrospinning method for self-assembled tree-like fibrous scaffolds: Microenvironment-associated regulation of MSC behavior and bone regeneration. (10th July 2022) - Kim, Jeong In; Kim, Ju Yeon; Kook, Sung-Ho; Lee, Jeong-Chae
Highlights: We fabricated biomimetic fibrous scaffolds via a novel electrospinning setup. The scaffolds present fibrillar microenvironments with microfiber/nanonet networks. The scaffolds differently regulate MSC behavior regarding to their fiber topographies. Topography-sensitive mechanosensing enhances osteogenesis and bone regeneration. The electrospun method provides an advanced approach for bone tissue engineering. Abstract: Numerous studies highlight advantages of electrospun scaffolds in bone tissue engineering, in which cellular behavior is tightly affected by fiber topographical cues of scaffolds. However, the classic electrospinning setup limits a desired presentation of biomimetic fibrous microenvironments that sense mechanosignaling and regulate stem cell behavior. The aims of this study were to fabricate advanced as-spun scaffolds presenting tree-like microfiber/nanonet networks and to evaluate their regulatory potentials on behavior of human mesenchymal stem cells (hMSCs) and bone regeneration. Here we developed a novel electrospinning setup that allowed the presentation of patterned Trunk microfibers (TMF) and/or branched nanonet fibers (BNnFs) in biomimetic fibrous scaffolds. As the cellular mechanisms, anisotropic-hierarchical topography of TMF controlled behavior of hMSCs through focal adhesion formation and Yes-associated protein (YAP) induction, whereas BNnF disturbed such mechanosensing responses in the cells. The fiber microenvironment-related expression and nuclear localization of YAP were. also correlated with the potentials of as-spun scaffolds to enhance osteogenic differentiation of the hMSCs and alveolar bone defect healing in an animal model. Collectively, this study provides an advanced approach of the modified electrospinning setup for presentation of biomimetic fibrillar microenvironments in as-spun scaffolds along with their application in stem cell behavior regulation and regenerative tissue engineering. Graphical abstract: Image, graphical abstract